Cysticercosis of cheek as a rare presentation: case report and review of literature - Shailendra Gautam; Monica Patnaik; Hitendra Prakash Singh; Shalini Bhalla (The Egyptian Journal of Otolaryngology, 2022)
Abstract Background Cysticercosis is caused by parasitic infestation of larval stage of pork tapeworm (Taenia solium). It is a result of accidental ingestion of contaminated water and food from eggs of tape worm due to poor sanitation. Pigs serve as intermediate host. The most common sites of cysticercosis are the muscles, heart, and liver but sites such as the tongue, buccal mucosa, cheek, or floor of mouth are rare. Case presentation A 10-year-old male patient presented to outpatient clinic of ENT department with gradually progressive swelling of right cheek. Patient has been managed with surgical excision of the cyst. Conclusion Cysticercosis can be a differential diagnosis for painless swelling at cheek.